Lower Bound of Circuit Complexity of Parity Function in a Basis of Unbounded Fan-In - Kombarov, Yu. A. (Moscow University mathematics bulletin, 2021)
The paper is focused on the implementation of parity functions by circuits in the basis . This basis consists of all gates that implement functions of the form . It is proved that every circuit in implementing a parity function of variables contains at least gates.